How 100-m event analyses improve our understanding of world-class men's and women's sprint performance - Slawinski, J.; Termoz, N.; Rabita, G.; Guilhem, G.; Dorel, S.; Morin, J.-B.; Samozino, P. (Scandinavian Journal of Medicine & Science in Sports, 2017)
This study aimed to compare the force (F)-velocity (v)-power (P)-time (t) relationships of female and male world-class sprinters. A total of 100 distance-time curves (50 women and 50 men) were computed from international 100-m finals, to determine the acceleration and deceleration phases of each race: (a) mechanical variables describing the velocity, force, and power output; and (b) F-P-v relationships and associated maximal power output, theoretical force and velocity produced by each athlete (Pmax, F0, and V0). The results showed that the maximal sprint velocity (Vmax) and mean power output (W/kg) developed over the entire 100 m strongly influenced 100-m performance (r > -0.80; P = 0.001). With the exception of mean force (N/kg) developed during the acceleration phase or during the entire 100 m, all of the mechanicals variables observed over the race were greater in men. Shorter acceleration and longer deceleration in women may explain both their lower Vmax and their greater decrease in velocity, and in turn their lower performance level, which can be explained by their higher V0 and its correlation with performance. This highlights the importance of the capability to keep applying horizontal force to the ground at high velocities.